Genomic and bioacoustic variation in a midwife toad hybrid zone: A role for reinforcement? - Johanna Ambu; Christophe Dufresnes (PLoS ONE)
Hybrid zones, i.e., geographic areas where diverging lineages meet, hybridize and eventually mix their genomes, offer opportunities to understand the mechanisms behind reproductive isolation and speciation. Hybrid zones are particularly well suited to study reinforcement, i.e., the process by which selection against hybridization increases reproductive barriers, which, in anuran amphibians, is typically expressed by increased divergence in advertisement calls-the main cue to assortative mating-in parapatric ranges. Using mitochondrial barcoding (16S sequences), population genomics (thousands of SNPs) and bioacoustic analyses (four call parameters), we examine the hybrid zone between two incipient species of midwife toads (Alytes obstetricans and A. almogavarii) in southern France, with the purposes of locating their transition, measuring genetic introgression, and documenting potential signatures of reinforcement. We map range boundaries in the Eastern Pyrenees and the southwestern foothills of the Massif Central, namely along the Ariège valley and the Montagne Noire area. Similarly to another transition between these species in Spain, we found the hybrid zone to be narrow, involving geographically restricted gene flow (~20 km wide allele frequency clines) and barrier loci (i.e., loci resisting introgression), both suggestive of partial post-zygotic isolation (hybrid incompatibilities). The calls of the species overlap less inside than outside the hybrid zone, due to a reduction of their standing variation rather than a shift towards distinctive variants. While neutral causes cannot be excluded, this pattern follows the general expectations of reinforcement, yet without reproductive character displacement. Our study highlights the potential of amphibian hybrid zones to assess the genetic and behavioral drivers of reproductive isolation in statu nascendi and under various evolutionary contexts.